Impact of Intense Physical Therapy on Mobility Outcomes in Acute Stroke Stratified by Cortical and Subcortical Stroke Location - Sinead Farrelly; Andrea D. Boan; Emily Monsch; Mark Bowden; Ramish Ramakrishnan; Steve Kautz; Christine Holmstedt (Journal of Acute Care Physical Therapy, 2026)
ABSTRACT Purpose: Poststroke rehabilitation is critical for functional recovery, yet the impact of stroke location on therapy response remains underexplored. Cortical and subcortical strokes differ in motor learning mechanisms, raising questions about the role of therapy frequency and the use of error augmentation training in early recovery. This post hoc analysis builds on previously published pilot data ( JACPT , July 2024) and aims to explore whether frequent error augmentation therapy (twice-daily sessions) improves functional outcomes in subcortical strokes similarly to cortical strokes. Methods: This secondary analysis included 96 patients with acute stroke enrolled in the initial pilot study who received either twice-daily error augmentation (EA) training or standard-of-care therapy sessions 3-5 times per week during hospitalization. EA training amplifies implicit movement errors to enhance motor adaptation. Functional outcomes, including the Postural Assessment Scale for Stroke (PASS), Activity Measure for Post-Acute Care (AM-PAC), and modified Rankin Scale (mRS), were analyzed using longitudinal mixed models, stratified by stroke location (cortical and subcortical). Results: The EA intervention group demonstrated significantly greater functional improvements than controls across both stroke subgroups. In subcortical strokes, postural balance gains from hospitalization to 90-day follow-up (PASS Total: 9.4 points) were comparable with those in cortical strokes (12.1 points), both significantly surpassing control group improvements. Similarly, AM-PAC mobility scores improved by approximately 3 points in both subcortical and cortical treatment subgroups compared with their respective controls. Conclusions: This secondary, exploratory analysis suggests that both increased therapy frequency and EA training may contribute to functional gains in subcortical strokes, with trends similar to those previously observed in cortical strokes. Although these findings expand upon prior work, they should be interpreted cautiously given the post hoc nature of this analysis. Further research is needed to confirm whether frequent EA training provides consistent benefits across stroke subtypes and to clarify the mechanisms underlying these potential effects.